A model based in the radius of vesicles to predict the number of unilamellar liposomes - Martinetti Montanari, Jorge Anibal (2014)
In particulate systems such as liposomes, concentration units are not enough to describe the drug distribution, as suspensions are not homogeneous. In certain in vitro assays, exposure to different number of particles introduces an extra variable regarding to contact phenomena. the aim is to achieve a rapid estimation of the number of unilamellar liposomes in a suspension. A simple mathematical method was developed; variables were the area and molecular weight of lipids, and the mean size of the liposomes. Unilamellar liposomes were prepared. Size was determined by dynamic light scattering, and then the number of particles were determined by tunable resistive pulse sensing. there was about a 90% coincidence between the theoretical results and the number of counted liposomes. This model could be useful for interpretation of in vitro experiments, when results could depend on the distribution of actives into different quantities of liposomes.